EFFECT OF PARETO OPTIMALITY IN MULTI OBJECTIVE OPTIMIZATION UNDER FUZZY ENVIRONMENT USING RANK AND DIVERSITY - Archiita Vijaykumar Malage (International Journal of Innovations in Engineering Research and Technology, 2022)
Study of multi objective optimization takes a major contribution in the field of research activities widely by the researchers due to the conflicting nature of ob- jectives.various works have been progressed to find details about pareto optimal solution.In continuation to this, researchers developed so many algorithms for more details about this work.Keeping inspired by Genetic algorithm, authors intend to show the consequences of pareto optimality of multi objective problems. Due to the volatile nature of decision maker, the concept of Fuzzy optimization has been introduced in correlating with the theory of optimization using several objectives. Here, authors discuss the result of pareto optimality under the influence of fuzzy parameters in terms of Rank,Diversity and Pareto efficiency. Different case studies have been analysed for more details about study of pareto optimality and it’s effects in involvement of fuzzy parameters.